BUSINESS SUSTAINABILITY ANALYSIS USING TRIPLE BOTTON LINE IN MALANG FURNITURE BUSINESS - Dullah, Mohammad; Anugrah, Roy; Hastutik, Sri; Puspitasari, Puspitasari (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Research related to furniture MSMEs in Malang needs to be carried out for several reasons to preserve culture: One of the unique and valuable forms of expression of culture is furniture crafts. Research related to sustainability in this industry will be very useful for preserving existing culture and traditions and can help the local government to maintain the existence of culture in the Malang area, increasing economic value. This research uses a qualitative approach. The results of the research are as follows: 1) That the Basuki Lacasa Art Gallery is a furniture industry that focuses on foreign buyers (export) so that it prioritizes quality, cultural characteristics of the archipelago, especially Singosari, handmade products so they have a character that is not the same as other products, or limited edition. Therefore, this product is rated higher than similar products and gets more appreciation from foreign buyers so that they can provide wages to their employees appropriately according to their work and have a partner company with similar, smaller companies to jointly develop the furniture business, 2) Basuki Lacasa Art Gallery is a furniture industry that treats employees financially and encourages workers to be creative and work optimally, collaborates with similar smaller businesses and ensures that customers (Buyers) get products that are safe, legal and limited. edition. 3) Sustainable perspective, of course the use of legal partners will give the owner a sense of comfort and can ensure the sustainability of raw materials that meet the criteria and can maintain the quality of the product itself, which in the end buyers can easily repurchase if the product meets the requirements. Their expectations and desires are that this company can also process waste wood chips through partners which are processed into products which are then resold by Basuki Lacasa Art Galeri.